COVID-19 and Acute Coronary Syndromes: Current Data and Future Implications - Cameli, Matteo; Pastore, Maria Concetta; Mandoli, Giulia Elena; D'Ascenzi, Flavio; Focardi, Marta; Biagioni, Giulia; Cameli, Paolo; Patti, Giuseppe; Franchi, Federico; Mondillo, Sergio; Valente, Serafina (Frontiers in Cardiovascular Medicine, 2021)
Coronavirus disease-2019 (COVID-19) pandemic is a global healthcare burden, characterized by high mortality and morbidity rates all over the world. During the outbreak period, the topic of ACS has raised several clinical issues, due to the risks of COVID-19 induced myocardial injury and to the uncertainties about the management of these cardiologic emergency condition, which should be organized optimizing the diagnostic and therapeutic resources and ensuring the maximum protection to healthcare personnel and hospital environment. COVID status should be assessed as soon as possible. Moreover, considerably lower rates of hospitalization for ACS have been reported all over the world, due to patients’ hesitations to refer to hospital and to missed diagnosis. As a result, short- and long-term complications of myocardial infarction are expected in the near future; this would require great efforts for healthcare providers to limit the effects of this issue. In the present review we discuss the impact of COVID-19 pandemic on ACS diagnosis and management, with possible consequences, providing an overview of the available evidence and suggesting future changes in social and clinical approach to ACS.